The effectiveness of the promotional mix in creating awareness to current and potential clients of the Institute of Engineers, Malaysia - Hamzah, Muhammad Hafiz (2009)
This research is about a study of the effectiveness of the promotional mix in creating awareness to current and potential clients of IEM. These promotional mixes which include direct marketing, advertising, publicity, sales promotion and personal selling are the factors that have been done by IEM in creating awareness to current and potential clients. This survey is conducted at Technip Geoproduction Kuala Lumpur which one of the largest engineering company in Malaysia. The sample size for this study is 80 respondents. There were 100 questionnaires being distributed and only 80 were return and completed. Data obtained using two methods that are primary and secondary data. Respondents are required to answer the questionnaires that contain promotional mix in creating clients awareness. Data are analyzed using Reliability Test, Frequency, Cross Tabulation and T-test through SPSS program. From the results, it was identified that direct marketing, advertising and sales promotion are the most effectiveness of the promotional mix that have been practiced by IEM in creating clients awareness. The result shows that all of the promotional mix that has been done by IEM is effective. Several recommendations could enhance IEM in improving their promotional mix in creating awareness to their clients.